2022
DOI: 10.1140/epjs/s11734-022-00650-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the basic reproduction number of COVID-19 from the incubation period distribution

Abstract: The estimates of the future course of spreading of the SARS-CoV-2 virus are frequently based on Markovian models in which the duration of residence in any compartment is exponentially distributed. Accordingly, the basic reproduction number R0 is also determined from formulae where it is related to the parameters of such models. The observations show that the start of infectivity of an individual appears nearly at the same time as the onset of symptoms, while the distribution of the incubation period is not an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…The study is performed employing four different approaches, and the results are found to behave in an "up-down-up" pattern and also help in predicting the workload of the healthcare systems and assist in the allocation of sufficient resources to the states in need. Markovian-type models for estimating the spread of the COVID-19 virus in the future considering the exponentially distributed time duration of the population in each compartment of the model are proposed by Basnarkov et al [29]. The study reveals that the starting time of the infection among individuals coincides with the same time as that of symptoms, while the incubation period is not exponentially distributed.…”
Section: Covid-19-related Estimations and Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study is performed employing four different approaches, and the results are found to behave in an "up-down-up" pattern and also help in predicting the workload of the healthcare systems and assist in the allocation of sufficient resources to the states in need. Markovian-type models for estimating the spread of the COVID-19 virus in the future considering the exponentially distributed time duration of the population in each compartment of the model are proposed by Basnarkov et al [29]. The study reveals that the starting time of the infection among individuals coincides with the same time as that of symptoms, while the incubation period is not exponentially distributed.…”
Section: Covid-19-related Estimations and Predictionsmentioning
confidence: 99%
“…This special issue is a compilation of original research articles that address the dynamics and applications of COVID-19 through nonlinear dynamics. The articles are organized in five sections, comprising mathematical modeling and epidemics [1][2][3][4][5][6][7], the dynamics of several waves and transmission [8][9][10][11][12][13][14][15][16][17], neural network and deep learning related to COVID-19 [18][19][20][21][22][23][24], predictions and estimations related to COVID-19 [25][26][27][28][29][30], and detailed analysis on the pandemic and its applications [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…1 Knowledge of incubation times helps in assessing the transmission potential of an infectious disease (Cheng et al, 2021;Basnarkov et al, 2022) as the incubation period can be used to estimate the reproduction number (i.e., the average number of secondary cases generated by an infector in a fully susceptible population). The incubation period is also of direct interest for case definition (Virlogeux et al, 2016) and to measure the effectiveness of contact tracing.…”
Section: Introductionmentioning
confidence: 99%